Crowding in during the Seven Years’ War - Nuno Palma; Carolyn Sissoko (Journal of Government and Economics, 2024)
We present a financial history of the Seven Years’ War (1756–1763) using a new dataset derived from the Bank of England minutes. We argue that the war and the associated actions of the Bank of England led to a transformation of the financial system. Additionally, while there was short-term crowding out of private investment when interest rates rose due to the issue of war-related government debt, in the long-run there was crowding in: government spending led to an increase in private sector investment.